Electrolyte Effects on Attachment of an Estuarine Bacterium - Gordon, Andrew S. (1984)
The effect of electrolyte concentration on attachment of Vibrio alginolyticus to hydroxyapatite was determined. Bacterial affinity for attachment to the surface and surface capacity were derived from linearization of bacterial adsorption isotherms. At low concentrations (<0.1 M) the affinity of the bacteria for the surface increased with increasing ionic strength, in agreement with the D.L.V.O. theory of colloid interaction. At higher concentrations, bacterial affinity for the surface decreased with increasing concentration of cations and was not related to ionic strength changes in the medium. These results demonstrate a change in the mechanism by which salts affect bacterial attachment at salt concentrations above 0.1 M. The results are consistent with the relationship between the proportion of attached bacteria and salinity observed in previously published field studies. The results may also resolve differences between various attachment studies carried out in different ionic strength media, utilizing different bacteria, surfaces, and experimental methods.